Central auditory development in children with hearing impairment: Clinical relevance of the P1 CAEP biomarker in children with multiple disabilities. (September 2013) - Sharma, Anu; Glick, Hannah; Campbell, Julia; Biever, Allison
Abstract: Objective: We review the development and plasticity of the central auditory pathways in infants and children with hearing loss who are fitted with cochlear implants (CIs). Secondly, we describe case studies demonstrating the clinical utility of the P1 central auditory evoked potential (CAEP) for evaluating cortical auditory maturation in the rapidly increasing number of cochlear-implanted children who have multiple disabilities. Study design: Children who receive CIs provide a platform to examine the trajectories of deprivation-induced and experience-dependent plasticity in the central auditory system. We review the evidence for, and time-limits of, sensitive periods for cortical auditory maturation framing an optimal period for cochlear implantation. Finally, we evaluate the use of the P1 biomarker as an objective assessment tool in the special case of children with multiple disabilities. Results: The P1 response was useful in assessing central auditory maturation in patients with CHARGE association, ANSD, and Pallister-Killian syndrome concomitant with hearing loss. Conclusion: The presence of coexisting disabilities in addition to hearing loss poses unique challenges regarding both pre-intervention evaluation and post-intervention rehabilitation for children with multiple disabilities. When combined with a standard audiological test battery, the P1 CAEP biomarker has a useful role in objectively evaluating the maturation of central auditory pathways to determine the effectiveness of various intervention strategies in hearing-impaired children with multiple disabilities.